2020
DOI: 10.1016/j.soilbio.2020.107962
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nitrogen addition differentially affects gross nitrogen transformations in alpine and temperate grassland soils

Abstract: Nitrogen (N) deposition can profoundly alter soil N cycling of grassland ecosystems.Substrates and soil acidification are expected to modify soil N transformations in response to elevated N deposition. Here, we carried out 15 N tracing studies to test the effects of N addition rates (low: 30 kg N ha -1 and high: 90/120 kg N ha -1 ) and soil acidification on gross N transformation rates using two typical Chinese grassland soils, an alpine calcareous soil and a temperate neutral soil. We found that N addition si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 84 publications
7
32
1
Order By: Relevance
“…Elevated N deposition affects terrestrial and aquatic ecosystems, with impacts on the soil N cycle, ecosystem functioning, and structures. , Knowledge of the source contributions of NH x deposition would benefit in evaluating the ecological risks and developing abatement strategies for agricultural and industrial activities. The quantified NH x dry deposition fluxes at the monitoring sites ranged from 6.0 to 65.6 kg N ha –1 yr –1 , with a mean of 21.0 kg N ha –1 yr –1 , higher than the national estimate of 12.2 kg N ha –1 yr –1 reported by Wen et al The dry deposition fluxes were estimated using the measured concentrations and modeled V d .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated N deposition affects terrestrial and aquatic ecosystems, with impacts on the soil N cycle, ecosystem functioning, and structures. , Knowledge of the source contributions of NH x deposition would benefit in evaluating the ecological risks and developing abatement strategies for agricultural and industrial activities. The quantified NH x dry deposition fluxes at the monitoring sites ranged from 6.0 to 65.6 kg N ha –1 yr –1 , with a mean of 21.0 kg N ha –1 yr –1 , higher than the national estimate of 12.2 kg N ha –1 yr –1 reported by Wen et al The dry deposition fluxes were estimated using the measured concentrations and modeled V d .…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, two background sites (DL and BK) were surrounded by temperate and alpine grasslands, respectively, but had similar seasonal variations to the rural sites, probably due to NH 3 emissions from several N addition experiments being conducted within 1 km of the two sampling sites. 76 These spatial and seasonal differences across sites and seasons clearly indicate human activity-induced variations in NH 3 emissions and concentrations.…”
mentioning
confidence: 99%
“…I NH4 was significantly and positively correlated to M (Figure 2h). This indicated that decreasing NH 4 + substrates due to inhibitory effects on M was the most probable reason for altered NH 4 + immobilization rate in the areca nut plantations (Hao et al, 2020; Zhu et al, 2011). C/N ratio also remained unchanged (Table 1), indicating that the C/N ratio was not the main factor influencing N mineralization and immobilization processes of areca nut plantations in tropical regions.…”
Section: Discussionmentioning
confidence: 99%
“…The key factor was the decline in inorganic N production, for instance, the decline in M and O Nrec in long‐time areca nut plantations, which is related to agricultural practices, predominantly due to litter management. This decreased the levels of SOC and TN in areca nut plantations, with negative effects on M and O Nrec (Hao et al, 2018; Hao et al, 2020). Meanwhile, long‐term areca nut plantation induced soil acidification that could have also inhibited the gross N mineralization rates, limiting the INS.…”
Section: Discussionmentioning
confidence: 99%
“…The various experimental results from different individual studies were reported in grassland ecosystems that had been conducted to explore how N deposition or fertilization affects N turnover processes in grassland ecosystems, especially in soil N turnover (i.e., N ammonification, nitrification, denitrification, and immobilization) and total N pool [ 18 , 19 ]. Previous studies showed that N addition increased, decreased, or had no effects on soil N turnover [ 14 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%